Opportunities for business services in the CARIFORUM-EC Economic Partnership Agreement \n (The Unit BridgetownBB, 2010)
Outlines the key EPA-related provisions on trade in services; commitments made by the European Union granting market access for professional and other business services from CARIFORUM; and the range of services which can be provided by Barbadian businesses via the cross-border supply of services provisions
Keywords: PARTNERSHIP